2005
DOI: 10.1097/00000542-200510000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Anesthetics Bind Rat Synaptic Snare Proteins

Abstract: SNARE proteins are potential synaptic targets of volatile anesthetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 33 publications
3
49
1
Order By: Relevance
“…While anesthetic interactions with other SNARE and/or SNARE-related proteins are possible, our data raise the possibility that syntaxin 1A is involved in the response to isoflurane. This hypothesis is supported by NMR binding studies demonstrating the ability of isoflurane to bind to syntaxin monomers (Nagele et al 2005). It is currently unknown whether the md130A mutant is capable of supporting exocytosis, although replacing wild-type syntaxin with the md130A mutant produced C. elegans that were not viable; animals that had both md130A and wild-type syntaxin were viable and were resistant to isoflurane (van Swinderen et al 1999).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…While anesthetic interactions with other SNARE and/or SNARE-related proteins are possible, our data raise the possibility that syntaxin 1A is involved in the response to isoflurane. This hypothesis is supported by NMR binding studies demonstrating the ability of isoflurane to bind to syntaxin monomers (Nagele et al 2005). It is currently unknown whether the md130A mutant is capable of supporting exocytosis, although replacing wild-type syntaxin with the md130A mutant produced C. elegans that were not viable; animals that had both md130A and wild-type syntaxin were viable and were resistant to isoflurane (van Swinderen et al 1999).…”
Section: Discussionmentioning
confidence: 94%
“…Behavioral sensitivity to isoflurane is significantly reduced in C. elegans heterozygous for the md130 mutation (van Swinderen et al 1999). In addition, isoflurane has been shown to bind to syntaxin 1A (Nagele et al 2005). To determine if md130A influences the isoflurane sensitivity of the mammalian neurotransmitter release machinery, PC12 cells were transfected with an md130A expression plasmid.…”
Section: Isoflurane Interacts With Syntaxin 1amentioning
confidence: 99%
“…anesthetics (42,43). Potential synaptic volatile anesthetic targets involved in regulating transmitter release include glutamate receptors, Na v channels (44), K 2P channels (45), nicotinic acetylcholine receptors (34), Ca v channels (46), neurotransmitter transporters (47,48), and SNARE proteins (8,49). Evidence suggests that the presynaptic effects of volatile anesthetics on neurotransmitter release are mediated by reduced nerve terminal excitability from inhibition of Na v channels rather than direct inhibition of Ca 2+ influx by inhibition of Ca v channels (7,44,50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Published evidence has suggested that anesthetic interactions with SNAP-25 and/or G␤ 4 might contribute to depressed neuronal signaling. For example, SNAP-25, a component of the ternary SNARE complex, binds volatile anesthetics at physiologically relevant concentrations (24), and isoflurane and propofol inhibit neurotransmitter release through interactions with SNAREs or associated proteins (25,26). Mutagenesis in SNARE complex proteins (including SNAP-25) alters organism sensitivity to general anesthetics (27).…”
Section: Discussionmentioning
confidence: 99%